Acupuncture for Subthreshold Depression: Study Protocol for a Randomized Controlled Trial - Xian, Jin; Wang, Ling; Sun, Mi; Wang, Xue; Zang, Xiao-Ming; Yu, Hui-Juan; Zhang, Xin; Cheng, Bin; Tan, Qi-Wen (Frontiers in Psychiatry, 2022)
Abstract Background: Subthreshold depression refers to a state of mental sub-health that has depressive symptoms but does not meet the diagnostic criteria for major depressive disorder. It is a strong risk factor for depression and is related to an increase in suicide and mortality. Studies suggest that acupuncture may be effective in the treatment of subthreshold depression, but no evidence has proven that the efficacy of acupuncture for subthreshold depression is a specific therapeutic effect or a placebo effect. Methods: This will be a prospective, randomized, controlled, and double-blind study of 64 patients with subthreshold depression. They will be randomly assigned as verum or minimal acupuncture group members. Patients in the verum acupuncture group will receive acupuncture at the acupoints, and those in the minimal acupuncture group will receive minimal acupuncture at nonacupoints. The interventions will be delivered over an 8-week period. The primary outcome measure will be the Hamilton Depression Scale-17 (HAMD-17). The secondary outcome measures will be the 9-item Patient Health Questionnaire (PHQ-9), 7-item Generalized Anxiety Disorder (GAD-7), and SF-12v2 Health Survey. The assessments will occur at baseline, 4 weeks, 8 weeks and during a follow-up period. Discussion: The protocol uses a randomized controlled trial to examine the effectiveness of acupuncture for subthreshold depression and to further study the mechanisms of its effect.